2020
DOI: 10.1101/2020.03.19.999060
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recollection-related hippocampal fMRI effects predict longitudinal memory change in healthy older adults

Abstract: Prior fMRI studies have reported relationships between memory-related activity in the hippocampus and in-scanner memory performance, but whether such activity is predictive of longitudinal memory change remains unclear. Here, we administered a neuropsychological test battery to a sample of cognitively healthy older adults on three occasions, the second and third sessions occurring one month and three years after the first session. Structural and functional MRI data were acquired between the first two sessions.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 71 publications
(59 reference statements)
1
9
1
Order By: Relevance
“…Loadings for each component are given in Supplemental Table 3. It is worth noting that the outcome of this PCA differs from those described previously by virtue of the absence of a 'speed' component (de Chastelaine et al, 2019;Hou et al, 2020;, reflecting the omission of the Trails scores. The factor loadings for the remaining components were unaffected by this omission.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 70%
See 3 more Smart Citations
“…Loadings for each component are given in Supplemental Table 3. It is worth noting that the outcome of this PCA differs from those described previously by virtue of the absence of a 'speed' component (de Chastelaine et al, 2019;Hou et al, 2020;, reflecting the omission of the Trails scores. The factor loadings for the remaining components were unaffected by this omission.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 70%
“…The benefits of this approach, along with more general issues concerning re-test effects, are discussed in detail in Hou et al (2020). We note, however, that our main findings in respect of relationships between cortical thickness and baseline performance, and of the relationships between thickness and memory change, were largely unaffected when either session 1 or session 2 scores alone comprised the estimates of baseline performance (see Supplementary materials).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…One study revealed a relationship of dedifferentiation of stimulus-specific processing in the lateral occipital cortex and parahippocampal place area and memory performance (Koen et al, 2019), but in that study, age and memory performance were independently associated with dedifferentiation (for a further discussion, see Koen and Rugg, 2019). Recently, recollection-related fMRI activation of the hippocampus during retrieval has been associated with both memory performance and longitudinal preservation of memory performance in older adults (Hou et al, 2020). While this approach will likely yield similar results to our whole-brain approach with encoding-related activation patterns, it may be limited in subjects with very poor memory performance, like individuals with subjective cognitive decline or mild cognitive impairment, especially considering that an associative word-pair learning task was used.…”
Section: Discussionmentioning
confidence: 99%